Language Borrowing between Arabic and Yoruba Language - Mahmoud-Mukadam, Abdur-Rasheed; Adebisi, Abdulwahid Aliy (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
Arabic Language is characterized by a great deal of influence that has made a profound impact on the rest of the world's languages, whether socially, culturally, religiously or economically. This language is specific to the Holy Quran, which has a higher constitution that Muslim takes from the laws of religion. Islam does not solve a place except it takes with language of its Arabic provisions. This article sheds light on some of the words borrowed by Yorba from Arabic in its various forms, of which there is no change in the image of pronunciation and what has undergone some change and distortion. The approach envisaged in this article is inductive, thus contributing in one way or another to supporting some scientific and historical facts in this area of borrowing. The results of this article is that language of the world is estimated relative to the world's speakers by 6.6% and the largest languages that borrow some others words in the corridors of life. Yorba, the language of southern Nigeria, and one of the three most famous tribal languages (Hausa, Yorba, Ibo) and which also has many of the speakers borrows many from Arabic.